Branding Strategy of Rumah Rempah Café Based on Regional Potential - Elis Anita Farida; Nuning Nurna Dewi; Khoiruddin Khoiruddin; Siti Intan Nurdiana Wong Abdullah (Yayasan Riset dan Pengembangan Intelektual, 2023)
Economic growth will be able to encourage increased economic growth, that is, business units carried out by individuals and companies. After the Covid-19 pandemic, various efforts have been made by the government to help businesspeople. Business branding is a classic problem often faced by business actors, especially in micro, small, and medium business units. Branding is a marketing method required to introduce a product. This study aimed to compare health drinks in the Spice House café in the Anwar Medika University environment. Efforts to improve product brand identity and introduce a stronger business brand image, so that these efforts will help the business achieve greater success in an increasingly competitive market. Through this branding strategy, businesses can become businesses that grow based on the brand they build. Branding can be remembered more easily, both in taste, location and the menu served at the Rumah Rempah Cafe, Anwar Medika University.